Palmitate increases Nur77 expression by modulating ZBP89 and Sp1 binding to the Nur77 proximal promoter in pancreatic β‐cells. Issue 23 (26th October 2013) - Mazuy, Claire; Ploton, Maheul; Eeckhoute, Jérôme; Berrabah, Wahiba; Staels, Bart; Lefebvre, Philippe; Helleboid-Chapman, Audrey
Abstract : Nur77 is a stress sensor in pancreatic β‐cells, which negatively regulates glucose‐stimulated insulin secretion. We recently showed that a lipotoxic shock caused by exposure of β‐cells to the saturated fatty acid palmitate strongly increases Nur77 expression. Here, using dual luciferase reporter assays and Nur77 promoter deletion constructs, we identified a regulatory cassette between −1534 and −1512 bp upstream from the translational start site mediating Nur77 promoter activation in response to palmitate exposure. Chromatin immunoprecipitation, transient transfection and siRNA‐mediated knockdown assays revealed that palmitate induced Nur77 promoter activation involves Sp1 recruitment and ZBP89 release from the gene promoter. Abstract : Nur77 promoter activity is regulated by palmitate in MIN6 cells. Palmitate treatment modulates the balance between ZBP89 and Sp1 binding to the Nur77 promoter. Activation of Nur77 promoter by palmitate is modulated by ZBP89 and Sp1.